2019
DOI: 10.1186/s40364-019-0163-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TCR Vβ11-2-Dβ1-Jβ1-1 T cell clone specific for WT1 peptides using high-throughput TCRβ gene sequencing

Abstract: We previously identified a TCR Vβ 21 T cell clone which was specific to CML patients, and demonstrated that TCR Vα 13/ β 21 gene-modified CD3 + T cells had specific cytotoxicity for HLA-A11 + K562 cells. However, it remains unclear which antigen is specifically recognized by the TCR Vβ 21 T cell clone. In this study, CD3 + T cells from healthy donor pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, Echchakir et al have reported high frequencies of Vβ5, Vβ20, and Vβ24 in patients with NSCLC ( 38 ). A previous work of ours demonstrated predominant expanded Vβ20-1 and Vβ29-1 in healthy human CD3 + T cells after WT1-specific antigen peptide or antigen BCR-ABL peptides induction ( 39 ). Notably, Vβ5 clone CD8 + T cells were related to antitumor activity in melanoma ( 40 ).…”
Section: Discussionmentioning
confidence: 66%
“…Interestingly, Echchakir et al have reported high frequencies of Vβ5, Vβ20, and Vβ24 in patients with NSCLC ( 38 ). A previous work of ours demonstrated predominant expanded Vβ20-1 and Vβ29-1 in healthy human CD3 + T cells after WT1-specific antigen peptide or antigen BCR-ABL peptides induction ( 39 ). Notably, Vβ5 clone CD8 + T cells were related to antitumor activity in melanoma ( 40 ).…”
Section: Discussionmentioning
confidence: 66%
“…Our team and other researchers have found that specific TCR Vβ clones may recognize leukemia-associated antigens in leukemia patients by polymerase chain reaction (PCR) and GeneScan. We also discovered that our previously identified chronic myeloid leukemia (CML)-associated TCR Vβ clone specifically recognizes Wilm’s tumor 1 (WT1) antigenic peptides by stimulating T cells in healthy donors with MHC-restricted antigenic peptides and TCR Vβ gene sequencing [ 26 ]. Recently, our team and partners have also found TCR Vβ clones that are closely related to the prognosis of lung cancer patients [ 27 ].…”
Section: Tcr-t Cell Constructionmentioning
confidence: 99%